Blame - Abbott, Jeff (Grand Central Publishing, 2017)
"Two years ago, Jane Norton crashed her car on a lonely road, killing her friend David and leaving her with amnesia. At first, everyone was sympathetic. Then they found Jane's note: I wish we were dead together... From that day the town turned against her. But even now Jane is filled with questions: Why were they on that road? Why was she with David? Did she really want to die? The secrets she should forget. Most of all, she must find out who has just written her an anonymous message: I know what really happened. I know what you don't remember..."--